An Analysis of Code-mixing and Code Switching by Online Tutor of Englishvit Video on Instagram Reels - Miladesia, Aulia Arifani (Journal of English for Specific Purposes in Indonesia, 2022)
English is the main act in communicating internationally. English is used as an official language in the global community to make anything that happens smooth and understanding, such as business field, medical, politics, and also education. Language courses are also not something unfamiliar in the countries, to reckon that is how important English to be mastered by people nowadays. The findings of this study should aid students and teachers in improving their understanding of how code-mixing and code-switching will affect students' skills in speaking English. The data for this sample is taken from an Instagram reels video from an English study account called Englishvit (@englishvit). The result shows that for code-mixing, the L1+L2 type is the highest percentage of lexical items. For codeswitching, L2 without translation is the highest percentage for the lexical items. The second rank for code-mixing is L2, and for codeswitching is L1+L2, which is the opposite of the highest rank. The certain expression that is often said in the reels video are have you guys know, hello, hi, thank you for watching, give comment down below, what do you think of, and bye-bye. L2 dominate in the conversation video because they have to demonstrate the situation based on the title of the video itself. The viewer can directly look at the example given in the video for understanding how to use the sentence or idiom or combine the words